Fracture toughness and hardness of transparent MgO–Al2O3–SiO2 glass-ceramics. Issue 7 (1st April 2022) - Sant'Ana Gallo, Leonardo; Célarié, Fabrice; Bettini, Jefferson; Rodrigues, Ana Candida M.; Rouxel, Tanguy; Zanotto, Edgar D.
Abstract: Hard and strong transparent glass-ceramics (TGCs) can be used as cooktop plates, telescope mirrors, armor materials, and screens for smartphones and tablets. In this work, transparent glass-ceramics from the MgO–Al2 O3 –SiO2 (MAS) system were obtained after a refined heat-treatment protocol. The evolution in fracture toughness, KIC (Single Edge Precracked Beam), and Vickers hardness (HV ) were characterized as a function of the crystallization progress. The KIC of the parent glass was 0.6 MPa m 1/2, whereas the TGC samples present values around 1.1 MPa m 1/2 . The average glass hardness was 8.5 ± 0.8 GPa for loads of 0.6–5 N, whereas the HV of the TGC samples varied from 9 to 10 GPa, for indentation loads ranging from 4.9 to 9.8 N. These results are discussed in light of our previous findings on the evolution of elastic modulus in the same glass-ceramics.